Strategi Adaptasi Mahasiswa Gen Z terhadap Trend Velocity dalam Pembelajaran dan Kehidupan Sosial - Wafiq Maulana Ibrahim; Dany Miftah M. Nur (Yayasan Literasi Sains Indonesia, 2025)
In the digital era marked by the acceleration of trend Velocity changes, especially through platforms such as TikTok, Generation Z students are required to have high adaptability to face challenges in learning and social life. This study aims to explore the adaptation strategies implemented by Gen Z students in responding to the rapid changes in trends, both in academic contexts and social interactions on campus. With a qualitative descriptive approach, data were collected through direct and indirect interviews and open questionnaires via Google Form. Informants were selected purposively, namely those who are active in digital learning and campus organizational activities. The results show that students utilize digital media to create educational content such as learning videos, vlogs, and digital campaigns, and are able to manage the content production process efficiently following the latest trends. Socially, they are active in organizing and interacting through digital communities, showing short, fast, and platform-based communication patterns. Campus organizations become a space for developing soft skills and digital networks. In conclusion, Gen Z students are adaptive to the dynamics of digital trends through the use of technology, content creativity, and integration of online-offline activities. They rely on platforms such as YouTube, Google Scholar, and e-learning, and are active in building social networks. However, they also face challenges in the form of digital distractions and existential pressures that are addressed through selective time and information management strategies.